1992
DOI: 10.1042/bj2860681
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol increases receptor-dependent cyclic AMP production in cultured hepatocytes by decreasing Gi-mediated inhibition

Abstract: Increasing evidence suggests that ethanol-induced changes in cyclic AMP (cAMP) signal transduction play a critical role in the acute and chronic effects of ethanol. Here we have investigated the effects of ethanol on cAMP signal transduction in primary cultures of rat hepatocytes. Acute exposure to ethanol had a biphasic effect on glucagon-receptor-dependent cAMP production in intact cells: 25-50 mM-ethanol decreased cAMP, whereas treatment with 100-200 mM-ethanol increased cAMP. After chronic exposure to 50-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 43 publications
0
36
0
Order By: Relevance
“…Although the consensus sequence for CRE is not present in the t-PA promoter, a functional CRE-like element has been identified, which acts synergistically with a putative AP-2 binding site to induced t-PA gene transcription by phorbol 12-myristate 13-acetate (22). Indeed, previous studies have shown that cholera toxin and dibutyryl-cAMP can directly induce t-PA gene transcription in rat hepatocytes (30,31). Furthermore, we have previously shown that low concentrations of alcohol enhance isoproterenol-induced t-PA gene transcription via increase in cAMP levels and induction of CRE promoter activity in vascular endothelial cells (32).…”
Section: Effects Of Eets and Cyp2j2 On T-pa Gene Transcription-mentioning
confidence: 74%
“…Although the consensus sequence for CRE is not present in the t-PA promoter, a functional CRE-like element has been identified, which acts synergistically with a putative AP-2 binding site to induced t-PA gene transcription by phorbol 12-myristate 13-acetate (22). Indeed, previous studies have shown that cholera toxin and dibutyryl-cAMP can directly induce t-PA gene transcription in rat hepatocytes (30,31). Furthermore, we have previously shown that low concentrations of alcohol enhance isoproterenol-induced t-PA gene transcription via increase in cAMP levels and induction of CRE promoter activity in vascular endothelial cells (32).…”
Section: Effects Of Eets and Cyp2j2 On T-pa Gene Transcription-mentioning
confidence: 74%
“…It is possible that the increase in iloprost stimulation is due to a chronic ethanol-induced increase in IP receptor number, since chronic ethanol has recently been reported to increase expression of b-opioid receptor, a2-adrenoceptor and muscarinic acetylcholine receptor expression in NG108-15 cells Hu et al, 1993 (Nagy & DeSilva, 1992) and human placental trophoblasts (Karl et al, 1994). Thus the chronic ethanol-induced increase in cyclic AMP accumulation is a characteristic of different cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Nagy reported that acute exposure of primary rat hepatocyte cultures to ethanol increases the extracellular adenosine concentration ( 19 ), and that ethanol increases cAMP production in cultured hepatocytes via an adenosine receptor-dependent mechanism ( 23 ). Adenosine receptors have been divided into three major subclasses, A1, A2, and A3.…”
Section: Discussionmentioning
confidence: 99%